Space planning determinants to achieve acoustical comfort in libraries: a literature review / Norlyadis Zamin, Azizah Md Ajis and Asmat Ismail - Zamin, Norlyadis; Md Ajis, Azizah; Ismail, Asmat (2021)
Library spaces nowadays exhibit a wide range of acoustic quality since it provides spaces for 'reading and thinking' as well as spaces for 'communicating and interacting' to be suited with current learning practices, whether in schools, universities or public libraries. Planning a space to cater for various activities in a library will be complex and need a conscientious approach to ensure the occupants experience the acoustical comfort thus achieving quality learning conditions. This paper aims to review the determinants of space planning criteria towards the library's acoustical comfort. The paper presents a discussion on the space planning components, sustainable standard, noise sources and acoustical comfort. The findings provide an insight for researchers interested in acoustic comfort and sustainable space planning for libraries.